APLIKASI INFORMASI TARI TRADISIONAL DI JAWA TENGAH DENGAN WebGIS (Information Technology and Telematics, 2014)
Abstract— Central Java is one of provinsion in Indonesia whict have many cultures and many important histories for this country. One of those culture which the most complex which has magic history and tradition culture is art of traditional dance Traditional dance from the first coming and meaning of the story accept become also one of tradition in a ritual and important ceremonial. moreover one of the traditional dance in central java which is allowed to show in sacral event in a kingdom. but now, in a growing up from traditional dance of central java is going last and not little witch the histories is starting lost. and undetected. the mining of attention with traditional culture become one of factor the weeknes attention culture in this central java. this art of traditional dance SIG application in mode for helping and saveing this culture, art of traditional dance in  central java and make easy for breaking for same information about traditional dance in central java. with some feature to be get more information from user to know some information. to know where and information of the traditional dance.